Pelatihan Penelusuran Bakat dan Minat dengan Pendekatan Multiple Intelegences di MA Midanut Ta’lim Jogoroto Jombang - Oktaffi Arinna Manasikana; Andhika Mayasari; M. Bambang Edi Siswanto; Ita Rahmania Kusumawati; Andri Wahyu Wijayadi; Noer Af’idah; Dewi Kusumaningsih (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2022)
Interests and talents have a very big influence in achieving educational, job, position, or career achievements. Multiple Intelligences or multiple intelligences are various skills and talents that students have to solve various problems in learning and life. MA Midanutta'lim students Jogoroto Jombang do not yet know the urgency of talent and interest in achieving academic and career achievements, nor do they recognize their own talents and interests. The service that is carried out for the students of MA Midanutta'lim Jogoroto Jombang is training to track students' talents and interests. The purpose of this interest and talent training using the Multiple Intelligences method is to find out the interests and talents and intelligence of MA Midanut Ta'lim Jogoroto Jombang students. Based on the results of the dedication that has been carried out, it can be concluded as follows: 1) The talent and interest search training activities through the Multiple Intelligences approach are running smoothly. 2) The highest intelligence is linguistic 69.23% and the least naturalist intelligence is 9.23%. From the results of the questionnaire on student responses to this training, most of them 98% agreed. This shows that the training received a good response.Keywords: interest; talent; multiple intelegences AbstrakMinat dan bakat sangat besar pengaruhnya dalam mencapai prestasi pendidikan, pekerjaan, jabatan, atau karir. Multiple Intelligences atau kecerdasan majemuk merupakan berbagai keterampilan dan bakat yang dimiliki siswa untuk menyelesaikan berbagai persoalan dalam pembelajaran dan kehidupan. Siswa MA Midanutta’lim Jogoroto Jombang belum mengetahui urgensi bakat dan minat dalam mencapai prestasi akademik dan karir, juga belum mengenali bakat dan minat yang ada pada diri mereka sendiri. Pengabdian yang dilakukan pada siswa MA Midanutta’lim Jogoroto Jombang adalah pelatihan penelusuran bakat dan minat pada siswa. Tujuan pelatihan minat dan bakat dengan metode Multiple Intelegences ini adalah untuk mengetahui minat dan bakat serta kecerdasan pada siswa MA Midanut Ta’lim Jogoroto Jombang. Berdasarkan hasil pengabdian yang telah dilakukan, dapat disimpulkan sebagai berikut: 1) Kegiatan pelatihan penelusuran bakat dan minat melalui pendekatan Multiple Intellegences berjalan lancar. 2) Kecerdasan terbanyak adalah pada linguistik 69,23% dan paling sedikit kecerdasan naturalis 9,23%. Dari hasil angket respon siswa terhadap pelatihan ini terbanyak 98% setuju. Hal ini menunjukkan pelatihan mendapat respon baik.Kata kunci: bakat; minat; multiple intelegences